Research on the Instability Mechanism and Control Technology of Gob-Side Entry in Deep Mines with Soft Rock - Lu Ma; Luyi Xing; Chang Liu; Tongyuan Cui; Xi Qiao; Wang Miao; Peng Kong (Buildings)
The gob-side entry driving in deep mines with soft rock exhibits a complex deformation and instability mechanism. This complexity leads to challenges in roadway stability control which greatly affects the coal mine production succession and safe and efficient mining. This paper takes the gob-side entry in Liuzhuang Coal Mine as the background. By adopting the method of theoretical analysis, a dynamic model of the roof subsidence in the goaf is established. The calculation indicates that achieving the stable subsidence of the basic roof and the equilibrium of the lateral abutment stress within the goaf requires a minimum of 108.9 days, offering a theoretical foundation for selecting an optimal driving time for the gob-side entry. The control technologies and methods of gob-side entry through grouting modification and high-strength support are proposed. Enhancing the length of anchor ropes and the density of bolt (cable) support to improve the role of the roadway support components can be better utilized, so the role of the support components of the roadway can be better exerted. The method of grouting and the reinforcement of coal pillars can effectively improve the carrying capacity of coal pillars. The numerical simulation is used to analyze the deformation law of gob-side entry. The study reveals significant deformation in the coal pillar and substantial roof subsidence, highlighting that maintaining the stability of the coal pillar is crucial for ensuring roadway safety. Following the grouting process, the deformation of the coal pillar and roof subsidence decreased by 16.7% and 7.1%, respectively. This demonstrates that coal pillar grouting not only mitigates pillar deformation but also provides effective control over roof subsidence. This study offers a quantitative calculation method to ascertain the excavation time of gob-side entry, and suggests that the application of high-strength support and the practice of coal pillar grouting can effectively maintain the steadiness of gob-side entry in deep mines with soft rock.